"In People's Faces for Lesbian and Gay Rights": Stories of Activism in Madison, Wisconsin, 1970 to 1990. (1st April 2016) - Seyforth, Scott C; Barnes, Nichole
Abstract: During the 1970s and 1980s, activists pushed Madison, Wisconsin, to the forefront of the national movement for gay rights. While midwestern participation in gay liberation has not been well documented or explored, the following article traces the role of local Madison organizers in this wider struggle for equality through the use of oral history. Using interviews from a collection of oral histories from the local LGBT community, this article chronicles the activism and political organizing that led to the early election of out officials, the nation's first statewide gay rights law, and campus protests over the ban on homosexuals serving in the military